Law Enforcement Views on Sex Offender Compliance with Registration Mandates - Walfield, Scott M. (American journal of criminal justice, 2017)
This exploratory mixed-methods study utilized data from 101 semi-structured interviews and a nationwide survey ( n = 765) to examine law enforcement perspectives on sex offender compliance with registration obligations. Specifically, law enforcement views were explored regarding the definitions and frequency of non-compliance, its underlying reasons or causes, and challenges and practices relating to its detection and management. Findings indicated that defining sex offender non-compliance with registration mandates is no simple task, but underscored the need to differentiate between purposeful and intentional forms of non-compliance and those that are less so. Data also support prior research indicating that few sex offenders truly abscond, and that most non-compliers are easily located. Detection of registration violators occurs through a number of means, and officers rely on community members, fellow law enforcement agents, and supervision partners to help monitor and manage their registrants. Variation exists between and within jurisdictions in terms of definitions, compliance management practices, and enforcement strategies. Translated into the domains of policy and practice, findings suggest that, rather than framing non-compliance under a single umbrella of “failure to register,” law enforcement efforts might be enhanced through improved typologies of non-compliance that can help to prioritize the use of enforcement resources.